2018
DOI: 10.1093/annonc/mdx759
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between patient-reported outcomes and clinical outcomes in metastatic castration-resistant prostate cancer: post hoc analysis of COU-AA-301 and COU-AA-302

Abstract: PROs are significantly associated with clinically relevant time-to-event efficacy outcomes in clinical trials and may complement and help predict traditional clinical practice methods for monitoring patients for disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…However, when In patients with metastatic castration-resistant prostate cancer, pain is generally reported alongside poor HRQoL and has been shown to be prognostic of overall and progression-free survival. 14,17 Although pain is not a salient symptom in patients with non-metastatic castration-resistant prostate cancer, 25 pain progression may be associated with disease progression in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when In patients with metastatic castration-resistant prostate cancer, pain is generally reported alongside poor HRQoL and has been shown to be prognostic of overall and progression-free survival. 14,17 Although pain is not a salient symptom in patients with non-metastatic castration-resistant prostate cancer, 25 pain progression may be associated with disease progression in this population.…”
Section: Discussionmentioning
confidence: 99%
“…12 Overall survival and disease progression outcomes are used to evaluate new treatment approaches, but to be truly valuable to patients, new treatments should not only delay disease progression but also maintain or, ideally, improve, health-related quality of life (HRQoL) without worsening symptoms. 13 Interestingly, HRQoL has been shown to be prognostic of survival in metastatic castration-resistant prostate cancer, 14,15 a finding that was confirmed by analysis of data from two phase 3 studies of enzalutamide in patients with metastatic castration-resistant prostate cancer. 16,17 In addition, HRQoL is central to cost-utility analysis in many countries and is increasingly influencing reimbursement decisions, especially for oncology treatments.…”
Section: Introductionmentioning
confidence: 92%
“…Due to the psychological implications of being diagnosed with metastatic disease, it is important to use patient-reported outcomes to match the instrumental data of MFS with the actual benefit in terms of both the delay of time to symptom worsening and global QoL. It is worth noting that in the most recent trials on PCa, the advantage in MFS is well supported by evidence of clinical benefit in terms of improvement in PFS on next-line therapy (PFS2),49 56 symptom delay and pain progression46 49 and QoL 48 49 57–63…”
Section: Bone Health During Nhtmentioning
confidence: 99%
“… 43‐46 A randomized trial showed that screening for these symptoms was associated with a 7‐month survival advantage over usual care, which in part may have been because patients in the intervention group had better performance status at progression and thus were more likely to receive optimal treatment 46,47 . Finally, several studies have shown that PROs enhance prediction of survival in myelodysplastic syndromes, 48 multiple myeloma, 49 early‐stage colorectal cancer, 50 advanced breast cancer, 51 metastatic castration‐resistant prostate cancer, 52 metastatic renal cell carcinoma, 53 advanced cancers, 54,55 and a variety of tumor types 56,57 . In fact, some data suggest that PROs predict survival better than provider‐rated performance status 58 …”
Section: The Need For Pghd In Cancer Carementioning
confidence: 99%